SINTAKSIS DAN REPRESENTASI PSIKOLOGIS TOKOH: KALIMAT MAJEMUK BERTINGKAT DALAM NOVEL ALMOND KARYA SOHN WON PYUNG - Shafariana; Johar Amir; Ambo Dalle; Tuti Wijayanti; Atikah Nurul Asda (SOSCIED, 2026)
Thus study aims to examine how complex sentences with subordination are used in the Indonesian-translated version of Almond, a novel by Sohn Won-Pyung, as a linguistic device to represent the psychological condition of the main character, Yoonjae, who suffers from alexithymia. Yoonjae is portrayed as an individual with difficulty identifying and expressing emotions, which significantly affects how he interacts with the world and conveys his inner experiences. In this context, the structure and form of language become crucial, as syntactic choices can function as representattions of emotional conflict that is not explicitly articulated. The study employs a qualitative-descriptive approach with a syntactic analysis method, combined with stylistic interpretation within a pyscholinguistic framework. Data were collected through documentation involving intensive reading of the novel and annotation of all complex sentences with subordination. The sentences were then analyzed based on types of subordinate clause relationships, including temporal, causal, conditional, and concessive relations. Form thw analysis of 187 complex sentences identified in the corpus data, six key finding were obtained. First, subordinated complex with emotional impairment (alexithymia). Second, the most frequent type of subordination is causal (33,29%), indicating a tendency for the caracter to rationalize experiences rather than respond affectively. Third, temporal and concessive structures play important roles in developing emotionally delayed and ambivalent narratives. Fourth, the syntactic complexity of the character’s language increases in the line with the development of his emotional sensitivity. At the beginning of the story, the sentence structures tend to be simple and informative, but the envolve into more refelective and complex forms as the character begins to recognize and engage with emotional experiences. Fifth, the sentence structure serves as an indicator of the character’s inner transformation, from emotionally flat to reflective and eventually empathetic. Sixth, syntax in this novel is note merely a structural element but also a strategic stylistic and representational tool used to subtly convey psychological dynamics. These finding suggest that syntax plays a crucial role in constructing and expressing a character’s psychological condition through an implicit strategy. Thus, complex sentences with subordination in Almond serve not only as grammatical structures but alos as effective linguistic tools that mirror the affective dynamics experienced by the protagonist, offering readers access to a nuanced and envolving emotional interior in literary narrative.